Quantitative Analysis of the Effects of Family and Social Environments on Early Childhood Learning Motivation in Gunung Mas Regency - Rudie Rudie; Febrianti Febrianti; Aras Anggelina (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to analyze the influence of the social and family environments on early childhood learning motivation in Gunung Mas Regency. It seeks to determine how these external factors, both individually and jointly, contribute to fostering children's enthusiasm, persistence, and positive attitudes toward learning during early education. Methodology: A quantitative research design employing a survey method was used. Data were collected using validated and reliable questionnaires distributed to 52 respondents, comprising parents and teachers at TK Pembina Manuhing Raya in Gunung Mas Regency. The data were analyzed using SPSS version 25 to examine the partial and simultaneous effects of the social environment (X₁) and the family environment (X₂) on learning motivation (Y). Main Findings: The findings revealed that both the social environment (t = 3.911; Sig. = 0.000 < 0.05) and the family environment (t = 9.361; Sig. = 0.000 < 0.05) have a significant, positive effect on early childhood learning motivation. Simultaneously, the two variables accounted for 50% of the variation in learning motivation (R² = 0.500), indicating that children’s motivation is substantially shaped by social and familial support. Novelty/Originality of this study: This research provides empirical evidence on the combined influence of family and social environments in shaping early childhood learning motivation within the cultural context of Central Kalimantan. It extends existing studies by quantifying the contributions of both environments and highlighting their complementary roles in early educational development.